Hydrogen sulfide induces Ca2+ signal in guard cells by regulating reactive oxygen species accumulation. (1st November 2020) - Gong, Chunmei; Shi, Cong; Ding, Xueting; Liu, Cuixia; Li, Jisheng
ABSTRACT: Hydrogen sulfide (H2 S) is an important gas signal molecule, but little is known about its signal mechanism. Ca 2+ is an important second messenger in plant cells, and its fluctuation in the cytoplasm causes downstream physiological responses. Our previous study found that H2 S can induce the accumulation of hydrogen peroxide (H2 O2 ). We also found that reactive oxygen species (ROS) can further induce the Ca 2+ influx in guard cells by noninvasive micro-teat technology (NMT). This study confirmed that the accumulation of reactive oxygen species to induce Ca 2+ signal in guard cells, resulting in stomatal closure. Thus, revealing a novel mechanism of H2 S promoting stomatal closure.